High-yield DNA extraction protocol for Azadirachta indica: overcoming metabolite interference - Rimpee Garg; Supriya Kaler; Ashok Kumar; Rama Kant (Academia Molecular Biology and Genomics)
Azadirachta indica (Neem), a tree of significant medicinal and ecological importance, poses challenges in genomic DNA extraction due to its high content of secondary metabolites, including polyphenols and polysaccharides, which impede downstream molecular applications. The aim of this study was to develop a reliable DNA extraction method suitable for metabolite-rich tissues of Azadirachta indica. This study presents an optimized, cost-effective, and high-throughput protocol based on a modified CTAB method. The protocol incorporates an initial sorbitol wash step to minimize contaminants, followed by CTAB extraction and a modified purification process. Genomic DNA was extracted from the leaf tissues of ten indigenous accessions, consistently yielding high-quality DNA with concentrations ranging from 433 to 995 µg/mL and a purity ratio around A260/A280 ≈ 1.8. DNA integrity and suitability for molecular applications were confirmed through agarose gel electrophoresis, spectrophotometric analysis, and successful amplification using Simple Sequence Repeat (SSR) markers. Compared to the existing protocols, the method offers improved yield, purity, and reproducibility, making it a reliable tool for molecular studies and genetic diversity assessment in A. indica and potentially other metabolite-rich plant species.